2021
DOI: 10.1007/s10006-021-00981-9
|View full text |Cite
|
Sign up to set email alerts
|

Top 100 cited systematic reviews and meta-analyses in the major journals of oral and maxillofacial surgery: a bibliometric analysis

Abstract: Background : The aim of this bibliometric research was to identify and analyze the top 100 cited systematic reviews in the eld of oral and maxillofacial surgery.Methods : Using the Web of Science-database without restrictions on publication year or language, a bibliometric analysis was performed for the ve major journals of oral and maxillofacial surgery: International

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 8 Older articles receive more citations than recently published ones, due to the advantage of time and the snowball effect of subsequent related articles referring to older and primary articles. 8 , 19 Correlating with other studies, 19 , 20 more cited articles were published after 2010, highlighting the scientific expansion in Orthodontics focused on clinical trials and evidence-based practice. It is important to note that in the Cochrane Database of Systematic Reviews (IF: 8.4), an internationally recognized evidence-based Medicine journal, a handful of articles (n=5) were published.…”
Section: Discussionmentioning
confidence: 57%
“… 8 Older articles receive more citations than recently published ones, due to the advantage of time and the snowball effect of subsequent related articles referring to older and primary articles. 8 , 19 Correlating with other studies, 19 , 20 more cited articles were published after 2010, highlighting the scientific expansion in Orthodontics focused on clinical trials and evidence-based practice. It is important to note that in the Cochrane Database of Systematic Reviews (IF: 8.4), an internationally recognized evidence-based Medicine journal, a handful of articles (n=5) were published.…”
Section: Discussionmentioning
confidence: 57%
“…As in the field of oral and maxillofacial surgery [ 14 ], most (81 of 100) of the top-cited studies were from the USA and Europe. However, this was not a surprising finding since it has been shown that most of the top-cited or top-ranked studies are conducted in countries with better economic rankings [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A bibliometric analysis was performed to rank the top 100 cited papers related to the field of TMD. This study followed the same methodology applied in previous studies that analyzed the top 100 cited papers in robotic [ 13 ] and oral and maxillofacial surgery [ 14 ]. The search strategy was performed on November 18, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…A recent bibliometric analysis has suggested that out of the top 100 cited systemic reviews and meta-analyses in our specialty, only 10 are pertaining to maxillofacial trauma. 15 It is reasonable to believe that baby steps in the direction of merging the art of surgery with the science of it would have a major impact on the patient care that we provide!…”
mentioning
confidence: 99%